Genocide concept in Lithuanian history - Anušauskas , Arvydas (Genocidas ir rezistencija, 2001)
The term ‘genocide’ has appeared in Lithuanian historiography relatively recently, which may be the reason why its usage varies so much. It can be said that there are different viewpoints justifying or denying the use of the term to describe different methods of annihilation of people or different groups of people. It can be said that the term ’genocide’ has been definitively adopted in Lithuanian historiography over the last five years, but its concept is not sufficiently aligned with the meaning of the concept in the International Convention. It is noted that the original concept of ‘genocide’ is used, and that reference is made to subsequent first draft definition of ‘genocide’, which also includes the ‘annihilation of political groups’ and cultural genocide (ethnocide). Meanwhile, ‘genocide’, like any concept, must be used clearly and consistently.